Measurement of the Λb lifetime in the exclusive decay Λb→J/ψΛ - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We have measured the Λb lifetime using the exclusive decay Λb→J/ψΛ, based on 1.2fb-1 of data collected with the D0 detector during 2002-2006. From 171 reconstructed Λb decays, where the J/ψ and Λ are identified via the decays J/ψ→μ+μ- and Λ→pπ, we measured the Λb lifetime to be τ(Λb)=1.218-0.115+0.130(stat)±0.042(syst)ps. We also measured the B0 lifetime in the decay B0→J/ψ(μ+μ-)KS0(π+π-) to be τ(B0)=1.501-0.074+0.078(stat)±0.050(syst)ps, yielding a lifetime ratio of τ(Λb)/τ(B0)=0.811-0.087+0.096(stat)±0.034(syst). © 2007 The American Physical Society.